(untitled) (Literary Voice, 2025)
This article explores the philosophical dimensions of Puran Singh’s The Spirit of Oriental Poetry, examining his integration of mysticism, spirituality, and poetic expression. Singh perceives poetry as a divine revelation, distinguishing Eastern poetry’s transcendental essence from the materialistic tendencies of Western literature. Through his discussions on poets like Whitman, Blake, Rumi, Guru Nanak, and Kabir, Singh underscores poetry’s role in spiritual awakening. His critique of Western rationalism highlights the erosion of poetic intuition, advocating for a return to poetry as a means of divine communion. By positioning poetry as a bridge between the human and the divine, Singh reaffirms its metaphysical significance. This study contextualizes Singh’s work within comparative literature and mystical philosophy.